Men or babies, that is the question: Working memory as a function of menstrual cycle - Vranić, Andrea (Array, 2005)
It has been shown repeatedly that estrogen enhances various memory functions. The aim of this study was to explore the influences of task content and estrogen level on working memory performance. We hypothesized that a shift in attention toward evolutionary relevant stimuli in different phases of menstrual cycle might occur. Therefore, we used two sets of cards in a memory game, one with photographs of adult male faces, and the other one with photographs of babies. Two groups of women were tested: with regular menstrual cycles (n=56) and on oral contraceptives (n=16). The performance on the task had the same pattern in both groups: women were significantly more efficient in recognizing male faces during high-estrogen phases of the cycle than in low-estrogen phases, while the recognition of baby faces did not change during cycle. Results are discussed in terms of importance of shifts in attention toward evolutionary relevant stimuli.